ANALISIS RESEPSI MAHASISWA UMY, UNY, DAN UGM TERHADAP REPRESENTASI GENDER DALAM IKLAN PRODUK ALKOHOL DI MEDIA DIGITAL - Tsauri Nur Firdaus; Kevin Tjeunfin; Muhammad Faishal Laitupa; Fajar Junaedi (Konvergensi, 2026)
This study aims to evaluate gender representation and meaning formation in alcohol product advertisements in digital media, as well as to investigate how adolescent audiences receive these messages through Stuart Hall's Encoding/Decoding Theory. This situation arises alongside the increasing prevalence of alcohol marketing on social media, which often highlights themes of freedom, modernity, and pleasure, but may conflict with the cultural and religious values of Indonesian society. This study uses a qualitative methodology through a case study approach, involving eight student participants from Muhammadiyah University Yogyakarta (UMY), Yogyakarta State University (UNY), and Gadjah Mada University (UGM). Data was collected through comprehensive interviews and visual documentation of advertisements on Instagram, then evaluated using NVivo 12 Plus software to generate topic classifications and audience reaction patterns. The results show that the encoding process reflects symbols of freedom, sensuality, and urban lifestyles associated with courage and independence. In the decoding process, the audience demonstrated three positions of acceptance: hegemonic-dominant, negotiated, and oppositional, with most respondents in the negotiated and oppositional positions rejecting the normalisation of alcohol and gender bias. This study confirms that young Indonesian audiences are active readers who understand media messages from the perspective of moral values, religion, and local culture. These findings highlight the importance of critical media literacy and ethical principles related to digital advertising laws in Indonesia.